Bibliographic information in digital culture: on the discussion problems and the results of the III International Bibliographic Congress - A. Е. Guskov; О. N. Zlobinskaya; D. V. Kosyakov; N. К. Lelikova; О. L. Lavrik (Библиосфера)
The present review and analytical article devoted to the III International Bibliographic Congress provides general information about the most acute problems of modern bibliographic activity and the Congress as a whole, offers points of view on the main debatable issues: about the MARC format, DOI and bibliographic reference, national bibliographic resources.